SIGNIFICANCE AND IMPORTANCE OF METAPHOR IN LINGUISTIC SCIENCE - Ulugova Shokhida Shokhrukhovna; Samiyev Sanjar Akmal o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract. This article provides detailed information on the nature and types of metaphor. The article introduces the explanatory dictionary of the word metaphorical and analyzes several metaphorical terms in the Uzbek language. And, of course, we will see how it is used in sentences, what artistic coloring it gives to sentences when it is used. It also sheds light on the specific characteristics and meanings of "metaphor" in our culture!